Magnetic properties of Co/Pt multilayers based on magneto-optical effect - Quách, Duy Trường (Hue University Journal of Science: Natural Science, 2023)
Magnetic properties and domain structures of (Co-t nm/Pt-0,8 nm)5 (t = 0.3, 0.5, and 0.6) multilayers with perpendicular magnetic anisotropy fabricated by magnetron sputtering were investigated based on the magneto-optical (Kerr) effect. The results show that there are significant changes in their magnetic properties, as well as domain structures when increasing the thickness of the magnetic layers from 0.3 to 0.6 nm. With the increase of the thickness of the magnetic layers, the hysteresis loops of the multilayers change from circular-like to stripe-like structures. Furthermore, their magnetization reversals shift from being easy to completely reversible with small t and to being difficult to completely reversible with large t.